The Analysis of Tax Planning Implementation on Added Tax (Case Study at PT Toyotomo Indonesia and PT RKN Forge Indonesia) - Dian Hakip Nurdiansyah; Eva Theresna Ruchjana; Moriska Alfarisi (Universitas Warmadewa, 2020)
Tax is one of the main sources of state revenue. The bigger the tax, the better the state finances. However, for the taxpayers, tax payments are a burden. On the other hand, the company is subject to state tax because its’ activities are the tax object, which is a value-added tax. The aim of this study were to find out the policy of the implementation of Tax Planning of Value Added Tax implemented by PT Toyotomo Indonesia and PT RKN Forge Indonesia, to analyze the proper implementation of Tax Planning in the efficiency of the amount of Value Added Tax Payable, and to analyze the impact of the Tax Planning Implementation on Value Added Tax at PT Toyotomo Indonesia and PT RKN Forge Indonesia. The method used was descriptive quantitative. The data used in this research were primary and secondary data. The data collecting techniques used were interviews, observation, and documentation. The data analysis used was descriptive quantitative analysis with study case approach. The results of the research of Taxation Implementation at PT Toyotomo Indonesia and PT RKN Forge Indonesia related to Value Added Tax to efficient the VAT payable is good and in accordance with the applicable tax regulation. The impact of the tax planning implementation on VAT is minimizing the taxes by conducting activities that are likely to minimize the tax costs such as tax saving, avoiding violations of tax regulations, optimizing the creditable input tax, utilizing the 0% tax facilities.